Is Dabigatran As Effective As Warfarin on Cardiac Thrombus in a Patient With Atrial Fibrillation? A Challenging Question. (May 2016) - Sunbul, Murat; Cincin, Altug; Mammadov, Ceyhun; Mutlu, Bulent
Abstract : Atrial fibrillation (AF) is an important risk factor for cardioembolic stroke. Warfarin is an effective treatment in reducing the risk of cardioembolic stroke in patients with AF. New anticoagulants have been widely using for stroke prophylaxis in patients with nonvalvular AF. Previous studies have suggested that thrombolytic therapy is effective treatment choice in patients with pulmonary embolisms. Warfarin therapy is also effective on prevention or treatment of cardiac thrombus in patients with AF. However, there are no evidence-based data on treatment of cardiac thrombus with new oral anticoagulants in patients with AF. In our case report, we reported an AF patient with cardiac thrombus and pulmonary embolism under dabigatran therapy.